Question

If a quadratic function has a vertex at (1, -4) and passes through the point (0, -3), write the equation in factored form.

Ask by Chandler Hamilton. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The quadratic function in factored form is \( y = (x - 3)(x + 1) \).

Solution

To find the quadratic function in factored form with a vertex at \((1, -4)\) and passing through the point \((0, -3)\), follow these steps: 1. **Start with the Vertex Form:** The vertex form of a quadratic function is: \[ y = a(x - h)^2 + k \] where \((h, k)\) is the vertex. Given the vertex \((1, -4)\), the equation becomes: \[ y = a(x - 1)^2 - 4 \] 2. **Use the Given Point to Find \(a\):** Substitute the point \((0, -3)\) into the equation to solve for \(a\): \[ -3 = a(0 - 1)^2 - 4 \\ -3 = a(1) - 4 \\ a = 1 \] So, the vertex form is: \[ y = (x - 1)^2 - 4 \] 3. **Convert to Standard Form:** Expand the vertex form to get the standard quadratic form: \[ y = (x - 1)^2 - 4 \\ y = x^2 - 2x + 1 - 4 \\ y = x^2 - 2x - 3 \] 4. **Factor the Quadratic:** Factor \(x^2 - 2x - 3\): \[ y = (x - 3)(x + 1) \] **Verification:** - The roots are \(x = 3\) and \(x = -1\). - The axis of symmetry is \(\frac{3 + (-1)}{2} = 1\), which matches the vertex's x-coordinate. - Substituting \(x = 1\) into the equation gives \(y = -4\), confirming the vertex's y-coordinate. **Final Factored Form:** \[ y = (x - 3)(x + 1) \] **Answer:** After simplifying, a suitable factored form is (x – 3) multiplied by (x + 1). Thus, y = (x−3)(x+1)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To find the equation of the quadratic function in factored form, we start with the vertex form of a quadratic function, which is \(y = a(x - h)^2 + k\). Given the vertex (1, -4), we can express this as \(y = a(x - 1)^2 - 4\). Now, we need to determine the value of \(a\) by using the point (0, -3). Substituting (0, -3) into the equation gives us: \[ -3 = a(0 - 1)^2 - 4 \] \[ -3 = a(1) - 4 \] \[ -3 + 4 = a \] \[ a = 1 \] So the equation becomes \(y = (x - 1)^2 - 4\). Now, to express it in factored form, we can rewrite this as: \[ y = (x - 1 - 2)(x - 1 + 2) = (x - 3)(x + 1) \] Thus, the final equation in factored form is: \[ y = (x - 3)(x + 1) \]

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy